Human Resource Management Practices and Employee Knowledge Sharing Behavior: Mediating Role of Knowledge Sharing Intention - Amin , Mohammad Bin; Rubel , Mohammad Rabiul Basher (Asian Journal of Empirical Research, 2020)
The purpose of this study is to investigate the influences of HRM practices on knowledge sharing behavior with the mediating effect of knowledge sharing intention in the hotel industry of Bangladesh. This study assumes that knowledge sharing would be the most useful especially in service sectors like hotels (tourism). The cross-sectional dataset comprises of hotel employees is used for empirical analysis. The hypotheses were tested using Partial Least Square Structural Equation Modeling (PLS-SEM-2). The results show that among the four dimensions of HRM practices only compensation has a significant and positive relationship with knowledge sharing behavior. Whereas, with knowledge sharing intention three dimensions of HRM such as recruitment & selection, participation & compensation show significant influence. For mediation analysis, only training & development showed an insignificant mediating effect between HRM practices and knowledge sharing behavior. Such findings suggest that, if the management of the organizations gives proper concentration on HRM practices the outcome will be significant both for knowledge sharing and its intention.